Does Whistleblowing on Tax Evaders Reduce Ingroup Cooperation? - Chapkovski, Philipp; Corazzini, Luca; Maggian, Valeria (Frontiers in Psychology, 2021)
Whistleblowing is a powerful and rather inexpensive instrument to deter tax evasion. Despite the deterrent effects on tax evasion, whistleblowing can reduce trust and undermine agents’ attitude to cooperate with group members. Yet, no study has investigated the potential spillover effects of whistleblowing on ingroup cooperation. This paper reports results of a laboratory experiment in which subjects participate in two consecutive phases in unchanging groups: a tax evasion game, followed by a generalized gift exchange game. Two dimensions are manipulated in our experiment: the inclusion of a whistleblowing stage in which, after observing others’ declared incomes, subjects can signal other group members to the tax authority, and the provision of information about the content of the second phase before the tax evasion game is played. Our results show that whistleblowing is effective in both curbing tax evasion and improving the precision of tax auditing. Moreover, we detect no statistically significant spillover effects of whistleblowing on ingroup cooperation in the subsequent generalized gift exchange game, with this result being unaffected by the provision of information about the experimental task in the second phase. Finally, the provision of information does not significantly alter subjects’ (tax and whistleblowing) choices in the tax evasion game: thus, knowledge about perspective ingroup cooperation did not alter attitude towards whistleblowing.